Silvio Berlusconi: the businessman who became prime minister - Williams, Granville (Henry Stewart Talks, 2017)
The case study reviews how Silvio Berlusconi used his vast influence in the media industry in Italy to help him become prime minister three times, and how his control over broadcasting has put a choke on press freedom.